Mathematical modelling and simulation of battery electric vehicle based on backward-facing approach technique - Abulifa, A. A.; Che Soh, A.; Hassan, M. K.; Raja Ahamd, R. M. K.; MohdRadzi, M. A. (Science Research Society, 2021)
Proper and valid simulation of the Battery Electric Vehicle (BEV) is a preliminary step before proceeding to any extensive research for enhancing the BEV performance. Therefore, this study proposed with explanation the simulation of the main components of the BEV along with different validation tests. The proposed model is designed based on the actual components’ parameters using MATLAB-Simulink and ADVISOR tool. The vehicle is configured according to backward facing model and the design incorporates the technical specifications of a Malaysia local car, PROTON IRIZ (BEV). It is important to measure the model performance of BEV along with the main measure, which is the State of Charge (SoC), battery voltage, and driving cycles. For benchmarking the results are compared with different design proposed in the literature based on studies that uses New European Driving Cycle (NEDC), Urban Dynamometer Driving Schedule (UDDS) and Japanese 10- 15 Mode Driving Cycle (Japan 10-15).The result from the simulated design in MATLAB shows a valid result compared to the declared specifications of the PROTON IRIZ BEV vehicle. For instance, the results NEDC test revealed that the driving range has SoC 31884 seconds (298 Km), which is comparable to the PROTON IRIZ full range of 300 Km. This study presents a foundation support for further study in BEV.